Contact lens with variable structural color and preparation method thereof

By introducing periodic fold microstructures into contact lenses, using modulus difference to form structural color, and making it variable through environmental changes, the safety and single color problems of existing contact lenses are solved, and high light transmittance and The effect of multi-color contact lenses.

CN114839797BActive Publication Date: 2024-12-17SHENZHEN INST OF ADVANCED TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210375261.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-11
Publication Date
2024-12-17
Estimated Expiration
2042-04-11

AI Technical Summary

Technical Problem

The pigments or pigments in existing contact lenses may cause discomfort and allergic reactions in humans, and the reliability and safety of structural color contact lenses are difficult to guarantee. At the same time, the single color cannot meet the needs of multi-color contact lenses.

Method used

Using contact lenses with periodic wrinkle microstructures, multi-layer gels with high-modulus and low-modulus layers are formed by step-by-step polymerization curing and surface treatment, introducing modulus differences to generate structural colors and through environmental changes (e.g. Temperature and osmotic pressure) make the structure color change.

Benefits of technology

It realizes a safe and reliable structural color contact lens, improves light transmittance and oxygen transmission, meets the needs of multi-color contact lenses, and maintains efficient use when there is insufficient light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114839797B_ABST
    Figure CN114839797B_ABST
Patent Text Reader

Abstract

The present invention discloses a contact lens with variable structural color and a preparation method thereof, and belongs to the technical field of contact lenses. The iris area and / or pupil area of ​​the contact lens provided by the present invention has a wrinkle microstructure, which is a periodically arranged micro-nanoscale convex structure and concave structure, the height of the convex structure or the concave structure is 1nm-100μm, and the period is 1nm-100μm; the wrinkle microstructure forms a structural color in the contact lens. The present invention provides a multilayer gel with different moduli prepared by step-by-step polymerization and curing, or a single-layer gel is surface-treated to form a wrinkled microstructure to prepare a contact lens. The variable structural color contact lens provided by the present invention has the characteristics of simple preparation and controllable microstructure, which improves the safety of colored contact lenses and is suitable for human wear.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of contact lenses, and in particular relates to a contact lens with variable structural color and a preparation method thereof. Background Art

[0002] With the improvement of living standards, people no longer simply pursue practicality in glasses, but more aesthetics and safety. Contact lenses have developed rapidly in the past few decades, with the market share growing to more than 140 million people, becoming a symbol of people's pursuit of beauty and convenience in addition to being able to see the world clearly. Cosmetic lenses (also known as "beauty lenses"), originally launched by Johnson & Johnson and designed for the Asian market, add pigments or pigments to contact lenses to change the color of the eye's membrane, making it more charming, and gradually become popular among beauty lovers.

[0003] There are two problems with cosmetic contact lenses on the market: first, the added pigments or dyes can easily cause discomfort to the human cornea (such as foreign body sensation, congestion, fatigue, secretion, etc.), and even cause allergic reactions in patients in severe cases, leading to infection; second, the colors of cosmetic contact lenses on the market are relatively single, which cannot meet people's demand for multi-color cosmetic contact lenses. Recently, Shen et al. reported a method for preparing structural color contact lenses: core-shell polymer colloidal particles are introduced into contact lenses to form opal photonic crystal structures, and the prepared contact lenses can present bright structural colors (Shen, X., Du, J., Sun, J., Guo, J., Hu, X., & Wang, C. (2020). ACS Applied Materials & Interfaces, 12 (35), 39639-39648). However, there are two problems with chemically synthesized polymer microspheres: first, the colloidal particles are prone to defects during the self-assembly process, which affects the quality of the structural color and is difficult to prepare in large quantities, which reduces the cost and reliability of the structural color contact lenses obtained. Second, there is a difference in the refractive index between the colloidal particles and the contact lens substrate, which affects the light transmittance of the contact lenses, especially in scenes with insufficient light, which reduces their practicality. Therefore, it is particularly urgent to develop new structural color contact lens materials. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a contact lens with variable structural color and a preparation method thereof.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] On the one hand, the present invention provides a contact lens with variable structural color, wherein the iris area and / or pupil area of ​​the contact lens has a wrinkle microstructure, wherein the wrinkle microstructure is a periodically arranged micro-nanoscale convex structure and concave structure, wherein the height of the convex structure or the concave structure is 50nm-50μm, and the period of the convex structure or the concave structure is 10nm-20μm; the wrinkle microstructure forms structural color in the contact lens.

[0007] In the technical solution of the present invention, the wrinkle microstructure is a periodically arranged micro-nanoscale protrusion structure or depression structure, and the period is the distance between the centers of two adjacent protrusions / or depressions.

[0008] In some specific embodiments, the height of the protruding structures or the recessed structures is 10 nm, 50 nm, 100 nm, 500 nm, 1 μm, 20 μm, 50 μm or any height therebetween.

[0009] In some specific embodiments, the width of the protruding structure or the concave structure is 10 nm, 100 nm, 500 nm, 1 μm, 20 μm, 50 μm, 100 μm or any width therebetween.

[0010] Preferably, the contact lens comprises a low modulus layer, a high modulus layer and a wrinkle microstructure, wherein the high modulus layer is distributed on one side or both sides of the low modulus layer, and the wrinkle microstructure is distributed on the outer surface of the high modulus layer.

[0011] Preferably, the high modulus layer has a thickness of 1 nm-50 μm; and the low modulus layer has a thickness of 10 nm-1000 μm.

[0012] In some specific embodiments, the high modulus layer has a thickness of 1 nm, 50 nm, 100 nm, 500 nm, 1 μm, 20 μm, 50 μm, or any thickness therebetween.

[0013] In some specific embodiments, the high modulus layer has a thickness of 10 nm, 50 nm, 100 nm, 500 nm, 1 μm, 100 μm, 500 μm, 1000 μm, or any thickness therebetween.

[0014] Preferably, the modulus ratio of the high modulus layer to the low modulus layer is 2-10000.

[0015] In some specific embodiments, the modulus ratio of the high modulus layer to the low modulus layer is 2, 100, 1000, 5000, 10000 or any modulus ratio therebetween.

[0016] In the technical solution of the present invention, the contact lens is a temperature-responsive variable structural color contact lens or an osmotic pressure-responsive variable structural color contact lens. Specifically, when the wrinkle microstructure changes in the environment, such as when the external environment temperature changes or the body fluid osmotic pressure changes, the thickness and modulus of the high modulus layer and the low modulus layer change accordingly, thereby changing the periodicity of the wrinkle microstructure and thus changing the structural color.

[0017] The contact lens with variable structural color provided by the present invention has the following beneficial effects or advantages:

[0018] 1. The contact lens provided by the present invention introduces a periodic wrinkle microstructure through the interlayer modulus difference of the lens material, and its structure is stable and safe and reliable for the human body;

[0019] 2. The contact lens provided by the present invention has a periodic wrinkle microstructure that gives it a structural color, which can beautify the pupil while correcting vision. At the same time, the wrinkle microstructure can increase the specific surface area, promote oxygen penetration, and ensure corneal health;

[0020] 3. The contact lens provided by the present invention, due to the introduction of the wrinkle microstructure, the wrinkle cycle will change accordingly during the changes in the intraocular and extraocular environment (such as salt content, ambient temperature, etc.), thereby causing the structural color to change, thereby realizing the characteristic of variable structural color.

[0021] In another aspect, the present invention provides a method for preparing the above-mentioned contact lens with variable structural color, comprising the following steps:

[0022] (1) adding a contact lens precursor solution I into a contact lens mold, and polymerizing and curing the resulting contact lens to obtain a primary contact lens;

[0023] (2) placing the contact lens precursor solution II and the contact lens primary sheet obtained in step (1) in a contact lens mold for secondary polymerization, and then polymerizing and curing the contact lens precursor solution II on the surface of the contact lens primary sheet to obtain a contact lens primary sheet having a periodic wrinkle microstructure;

[0024] (3) Soaking the initial contact lens with a periodic wrinkled microstructure obtained in step (2) in saline to obtain a contact lens with a variable structural color.

[0025] Or the following steps:

[0026] (1) adding a contact lens precursor solution I into a contact lens mold, and polymerizing and curing the resulting contact lens to obtain a primary contact lens;

[0027] (2) performing surface treatment on the initial contact lens obtained in step (1) to obtain an initial contact lens having a periodic wrinkle microstructure;

[0028] (3) Soaking the initial contact lens with a periodic wrinkled microstructure obtained in step (2) in saline to obtain a contact lens with a variable structural color.

[0029] In the technical scheme of the present invention, a multilayer gel is prepared by step-by-step polymerization and curing, and the concentration of the initiator and the polymerization reaction conditions such as time are controlled to control the molecular weight and crosslinking degree of the polymer or the surface treatment is performed on the cured single-layer gel, so that the upper and lower layers of the contact lens gel material have different crosslinking degrees, thereby generating a modulus difference between the layers in the contact lens. During the step-by-step polymerization and curing, the gel of the high modulus layer is distributed on one side or both sides of the gel of the low modulus layer. Due to the difference in size and mechanical properties, a wrinkled microstructure is finally generated at the outer surface interface of the gel of the high modulus layer, and the wrinkled microstructure forms a structural color in the contact lens.

[0030] Preferably, the contact lens precursor solution I is selected from (a) a solution comprising a polymer; or, (b) a polymer solution comprising a polymer monomer, an initiator and a cross-linking agent;

[0031] Preferably, the polymer is selected from polymethyl methacrylate, polyhydroxyethyl methacrylate, polymethacrylate-2-hydroxypropyl, polyethoxyethyl methacrylate, polyhydroxypropyl methylcellulose, polyhydroxymethyl cellulose, polydimethylaminoethyl methacrylate, polyethylene glycol dimethacrylate, polyisobornyl methacrylate, polycellulose acetate butyrate, polysilicone methacrylate, polyfluorosilicone methacrylate, polyperfluoroether, poly N-vinyl pyrrolidone, polyvinyl alcohol, polyglycidyl methacrylate, silica gel, polydimethylsiloxane, polyparaxylene, Any one or copolymers of any of polylactic acid, polyethylene glycol, polypropylene oxide, polycaprolactone-polyacrylic acid, polylactide, poly(lactide-glycolide), polyacrylamide, poly-N-isopropylacrylamide, collagen, gelatin, guar gum, polyphosphazene, sodium alginate, chitosan, hyaluronic acid, alginic acid, cellulose, agarose, polyglucose, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene sulfonic acid, polyvinyl phosphoric acid, choline, polyethylene oxide, polyethyleneimine, polyethyleneamine, polyvinylpyridine, polyphosphate, polysilicate, polyamino acid and fibrin;

[0032] Among them, polyamino acids include poly-L-lysine, poly-L-glutamic acid, etc.;

[0033] Preferably, the initiator is selected from any one of an inorganic peroxide initiator, an azo initiator, a peroxide initiator and a photoinitiator;

[0034] Preferably, the cross-linking agent is selected from at least one of methylene bisacrylamide, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, divinyl benzene and derivatives thereof.

[0035] Preferably, the contact lens precursor solution II is selected from (a) a solution comprising a polymer; or, (b) a polymerization solution comprising a polymer monomer, an initiator and a cross-linking agent;

[0036] Preferably, the polymer is selected from polymethyl methacrylate, polyhydroxyethyl methacrylate, polymethacrylate-2-hydroxypropyl, polyethoxyethyl methacrylate, polyhydroxypropyl methylcellulose, polyhydroxymethyl cellulose, polydimethylaminoethyl methacrylate, polyethylene glycol dimethacrylate, polyisobornyl methacrylate, polycellulose acetate butyrate, polysilicone methacrylate, polyfluorosilicone methacrylate, polyperfluoroether, poly N-vinyl pyrrolidone, polyvinyl alcohol, polyglycidyl methacrylate, silica gel, polydimethylsiloxane, polyparaxylene, Any one or copolymers of any of polylactic acid, polyethylene glycol, polypropylene oxide, polycaprolactone-polyacrylic acid, polylactide, poly(lactide-glycolide), polyacrylamide, poly-N-isopropylacrylamide, collagen, gelatin, guar gum, polyphosphazene, sodium alginate, chitosan, hyaluronic acid, alginic acid, cellulose, agarose, polyglucose, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene sulfonic acid, polyvinyl phosphoric acid, choline, polyethylene oxide, polyethyleneimine, polyethyleneamine, polyvinylpyridine, polyphosphate, polysilicate, polyamino acid and fibrin;

[0037] Among them, polyamino acids include poly-L-lysine, poly-L-glutamic acid, etc.;

[0038] Preferably, the initiator is selected from any one of an inorganic peroxide initiator, an azo initiator, a peroxide initiator and a photoinitiator;

[0039] Preferably, the cross-linking agent is selected from at least one of methylene bisacrylamide, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, divinyl benzene and derivatives thereof.

[0040] In certain specific embodiments, the inorganic peroxide initiator includes but is not limited to ammonium persulfate, sodium persulfate, and potassium persulfate; the azo initiator includes but is not limited to azobisisobutyronitrile and azobisisoheptylnitrile; the peroxide initiator includes but is not limited to benzoyl peroxide and cyclohexanone peroxide; the photoinitiator includes but is not limited to diethoxyacetophenone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0041] Preferably, in step (3), the brine is selected from any one of a sodium chloride aqueous solution with a mass fraction of 0.89%, a sodium dihydrogen phosphate aqueous solution with a mass fraction of 0.1%, and a disodium hydrogen phosphate aqueous solution with a mass fraction of 0.6%.

[0042] Specifically, in step (3), the first contact lens is immersed in saline with a pH range of 5.0-9.0 for 2-24 hours.

[0043] Preferably, the surface treatment is selected from one or more of plasma treatment, ultraviolet light treatment, heat treatment, and tensile deformation.

[0044] In certain specific embodiments, the UV treatment requires coating the surface of the contact lens with an oligomer or monomer and a photoinitiator to initiate grafting, cross-linking or polymerization to achieve curing and increase the modulus.

[0045] In the technical solution of the present invention, the material of the contact lens mold is glass, quartz, polypropylene, polystyrene, polyethylene terephthalate or polycarbonate.

[0046] The method for preparing contact lenses with variable structural colors provided by the present invention generates a modulus difference in the lens through surface treatment or step-by-step polymerization and curing design, introduces periodic wrinkles, and generates structural colors, and the structural colors change with changes in the environment. The method can be used to prepare contact lenses with good safety, high light transmittance, bright and variable structural colors at low cost and high yield.

[0047] Compared with the prior art, the present invention has the following beneficial effects or advantages:

[0048] 1. Compared with the prior art, the method of the present invention adopts the raw materials for preparing contact lenses, without introducing additional pigments or raw materials, ensuring safety while making it highly transparent, not only forming structural color but also ensuring light transmittance, and it can still be used normally in situations with insufficient light.

[0049] 2. The present invention forms a wrinkled microstructure through a step-by-step polymerization curing or surface treatment method, which is safer, more controllable, and has a high yield rate than existing self-assembly methods and thin film processing methods. In addition, the structure obtained by this method has fewer defects and a more stable structure.

[0050] 3. The wrinkled layer obtained by the method of the present invention is a single layer, which is easier to control than the colloidal multilayer self-assembly method, and the process is simple, does not require additional chemical solvents, is safer, and is suitable for wearing. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 Schematic diagram of the color change of the contact lens with variable structural color in Example 1.

[0052] Figure 2 Schematic diagram of the structure of the contact lens with variable structural color in Example 1.

[0053] Figure 3This is a diagram of the wrinkle microstructure of the contact lens in Example 3. DETAILED DESCRIPTION

[0054] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0055] Example 1

[0056] In this embodiment, the contact lens with variable structural color is prepared by the following steps:

[0057] (1) Take a polycarbonate contact lens mold, which includes a separable upper mold and a lower mold, wherein the upper mold has a convex spherical surface and the lower mold has a concave spherical surface. Add a contact lens prepolymer solution into the mold: hydroxyethyl methacrylate and methylene bisacrylamide (mass ratio 50:1), use 2,2-diethoxyacetophenone (mass fraction is 0.5% of hydroxyethyl methacrylate) as an initiator, and cure it with 254nm ultraviolet light for 30 minutes to obtain a contact lens initial sheet;

[0058] (2) Adding a polymethyl methacrylate solution having a weight average molecular weight of 100,000 into a contact lens mold, placing the contact lens preform obtained in (1) into the contact lens mold, and subjecting the polymethyl methacrylate solution to 365 nm ultraviolet light curing for 30 minutes on the convex spherical surface of the contact lens preform. The modulus ratio of the polymethyl methacrylate layer to the polyhydroxyethyl methacrylate layer is 50:1, and a contact lens preform having a wrinkled microstructure is obtained.

[0059] (3) The contact lens with the wrinkled microstructure is immersed in a sodium chloride aqueous solution with a pH of 7.3 and a mass fraction of 0.89% until the expansion rate remains stable, thereby obtaining a contact lens with a variable structural color.

[0060] The contact lens in this embodiment includes a two-layer gel structure, wherein the high modulus layer, i.e., the polymethyl methacrylate layer, has a thickness of 10 nm, and the low modulus layer, i.e., the hydroxyethyl methacrylate layer, has a thickness of 20 μm. The wrinkle microstructure is distributed on the outer surface of the high modulus layer to form a periodically arranged uniform layer with a thickness of 30 μm. The period of the wrinkle microstructure, i.e., the distance between the centers of two adjacent protrusions / or depressions, is 700 nm.

[0061] The contact lens in this embodiment has a structure as follows Figure 2As shown: Layer 1 is a high modulus layer, and Layer 2 is a low modulus layer. The wrinkle microstructure is distributed on the upper surface of the high modulus layer 1 (not shown in the figure), that is, the outer surface.

[0062] The color change process of the contact lens in this embodiment is shown in FIG. Figure 1 , Figure 1 Middle: The structural color of the contact lens above is distributed in the iris area I, and the structural color of the contact lens below is distributed in the pupil area II. Its structural color is green when the ambient temperature is above 25 degrees Celsius, gradually changes from green to blue as the temperature drops from 4 to 25 degrees Celsius, and is blue below 4 degrees Celsius.

[0063] During the preparation process, different molds can be selected so that in step (2), polymethyl methacrylate is solidified on the convex and / or concave surfaces of zone I and / or zone II of the initial contact lens, so that the wrinkle microstructure is distributed in the pupil area and / or iris area.

[0064] Example 2

[0065] In this embodiment, the contact lens with variable structural color is prepared by the following steps:

[0066] (1) taking a polypropylene contact lens mold, the mold comprising a separable upper mold and a lower mold, wherein the upper mold has a convex spherical surface and the lower mold has a concave spherical surface, adding a contact lens prepolymer solution into the mold: methyl methacrylate, using 2-hydroxy-2-methyl-1-phenyl-1-propanone (mass fraction of 0.2% of methyl methacrylate) as an initiator, and curing with 365 nm ultraviolet light for 30 minutes to obtain a contact lens primary sheet with a thickness of 20 μm;

[0067] (2) The contact lens is placed in a plasma cleaning machine and treated with plasma at a voltage of 700 V for 15 minutes on the convex spherical surface to increase the modulus value of the surface. The thickness is 1 nm and the ratio of the Young's modulus of the high modulus layer to the low modulus layer is 100:1.

[0068] (3) The contact lens with a wrinkled microstructure is immersed in a sodium chloride aqueous solution with a pH of 7.3 and a mass fraction of 0.89% until the expansion rate remains stable, thereby obtaining a contact lens with a variable structural color.

[0069] The contact lens with structural color obtained in this embodiment has a convex layer of a high modulus layer with a thickness of 1 nm, and a concave layer of a low modulus layer with a thickness of 20 μm. The wrinkle microstructure is distributed on the outer surface of the high modulus layer to form a periodically arranged uniform layer with a thickness of 2 μm and a wrinkle period of 900 nm. The structural color of the wrinkle microstructure is distributed in the contact lens as a color element.

[0070] Example 3

[0071] In this embodiment, the contact lens with variable structural color is prepared by the following steps:

[0072] (1) Take a contact lens mold made of polymethyl methacrylate, which includes a separable upper mold and a lower mold, wherein the upper mold has a convex spherical surface and the lower mold has a concave spherical surface, and prepare a contact lens prepolymer solution: polydimethylsiloxane and its curing agent Sylgard184B are mixed in a mass ratio of 10:1, and the above mixture is mixed with n-hexane in a volume ratio of 1:1. Take 150 μL of the contact lens prepolymer solution and add it to the mold, and obtain a contact lens primary sheet by thermal curing at 50°C for 120 minutes;

[0073] (2) Placing the initial contact lens into a plasma cleaning machine and subjecting the convex spherical surface to plasma treatment at a voltage of 900 V for 5 min, thereby increasing the modulus value of the surface and forming an initial contact lens having a wrinkled microstructure, wherein the ratio of the Young's modulus of the high modulus layer to the low modulus layer is 1000:1.

[0074] (3) The obtained contact lens with wrinkled microstructure is immersed in a sodium chloride aqueous solution with a pH of 7.3 and a mass fraction of 0.89% until the expansion rate remains stable, thereby obtaining a contact lens with variable structural color.

[0075] In this embodiment, the thickness of the high modulus layer is 50nm, the thickness of the low modulus layer is 50μm, and the wrinkle microstructure is distributed on the outer surface of the high modulus layer. The thickness of the layer is 1μm, and the wrinkle period is 1100nm. The wrinkle microstructure is distributed in the contact lens as a color element.

[0076] The electron microscope image of the wrinkle microstructure of the contact lens prepared in this example is shown in Figure 3 From the figure, we can see that orderly and regular folds are formed on the surface of the film, and their period matches the wavelength of visible light, forming structural color.

[0077] Example 4

[0078] In this embodiment, the contact lens with variable structural color is prepared by the following steps:

[0079] (1) taking a polystyrene contact lens mold, the mold comprising a separable upper mold and a lower mold, wherein the upper mold has a convex spherical surface and the lower mold has a concave spherical surface, adding a contact lens prepolymer solution: polyvinyl alcohol and polyethylene glycol diacrylate (mass ratio of 40:1) into the mold, using 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone (mass concentration of polyvinyl alcohol 0.2%) as an initiator, and curing by 365 nm ultraviolet light for 30 minutes to obtain a contact lens primary sheet;

[0080] (2) The outer convex surface and the inner concave surface of the contact lens initial lens are spin-coated, and a polystyrene-polyvinyl pyridine (PS-b-P4VP) solution with a weight average molecular weight of 50,000 is spin-coated on the contact lens initial lens, and 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone (mass concentration is 0.2% of polystyrene-polyvinyl pyridine) is used as an initiator to perform 254nm ultraviolet curing to increase the Young's modulus of the surface and form a contact lens initial lens with a wrinkled microstructure, wherein the ratio of the Young's modulus of the high modulus layer to the low modulus layer is 20:1.

[0081] (3) The obtained contact lens containing the wrinkled microstructure is immersed in a sodium chloride aqueous solution with a pH value of 7.3 and a mass fraction of 0.89% until the expansion rate remains stable, thereby obtaining a contact lens with a variable structural color. The structural color is blue when the concentration of the environmental salt solution is above 1.0% and is blue when the concentration of the environmental salt solution is below 0.7%.

[0082] The contact lens in this embodiment includes a two-layer gel structure, the low modulus layer is a polyvinyl alcohol-polyethylene glycol diacrylate copolymer layer with a thickness of 200 μm, and the high modulus layer is a polystyrene-polyvinyl pyridine with a thickness of 20 μm.

[0083] The wrinkle microstructure is distributed on the outer surface of the high modulus layer to form a periodically arranged uniform layer with a thickness of 50 μm and a wrinkle period of 100 μm. The wrinkle microstructure is distributed in the contact lens as a color element.

[0084] Example 5

[0085] In this embodiment, the contact lens with variable structural color is prepared by the following steps:

[0086] (1) A polystyrene contact lens mold is obtained, the mold comprising a separable upper mold and a lower mold, wherein the upper mold has a convex spherical surface and the lower mold has a concave spherical surface, a contact lens prepolymer solution is added into the mold: polyvinyl alcohol and polyethylene glycol diacrylate (mass ratio is 40:1), 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone (mass concentration is 0.2% of polyvinyl alcohol) is used as an initiator, and a contact lens primary sheet is obtained by wavelength curing for 30 minutes;

[0087] (2) The obtained contact lens precursor is fixed, and a polycarbonate prepolymer with a molecular weight of 100,000 is cast on the contact lens precursor on the outer convex surface and the inner concave surface to obtain a contact lens precursor with a wrinkled microstructure, wherein the ratio of the Young's modulus of the high modulus layer to the low modulus layer is 10,000.

[0088] (3) The obtained photonic crystal structural color contact lens is subjected to secondary deposition, and the steps are the same as (2) to obtain a multilayer polymer sheet, and the structural color of the wrinkle microstructure is more obvious. When the ambient temperature rises to 32°C and the pH rises to above 7.8, the wrinkle structural color will change from green to red.

[0089] (4) The obtained contact lens having a wrinkled microstructure is immersed in a sodium chloride aqueous solution having a pH value of 7.3 and a mass fraction of 0.89% until the expansion rate remains stable, thereby obtaining a contact lens having a wrinkled microstructure.

[0090] The contact lens obtained in this embodiment has a double-layer gel, polyvinyl alcohol and polyethylene glycol diacrylate are low modulus layers with a thickness of 500 μm, and polycarbonate is a high modulus layer with a thickness of 10 μm. The wrinkle microstructure is distributed on the outer surface of the high modulus layer to form a periodically arranged uniform layer with a thickness of 50 μm and a wrinkle period of 400 nm. The wrinkle microstructure is distributed in the contact lens as a color element.

[0091] Example 6

[0092] The contact lens preparation method in this embodiment is the same as that in Embodiment 1, using contact lens molds of different thicknesses, with a high modulus layer thickness of 1 nm, a low modulus layer thickness of 10 nm, a modulus ratio of 2, a sheet layer thickness of 10 nm and a period of 10 nm formed by the wrinkled microstructure.

[0093] Example 7

[0094] The contact lens preparation method in this embodiment is the same as that in Embodiment 4, using contact lens molds of different thicknesses, with a high modulus layer thickness of 50 μm, a low modulus layer thickness of 1000 μm, a modulus ratio of 10000, a sheet layer thickness of 100 μm formed by the wrinkled microstructure, and a period of 100 μm.

[0095] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent transformation made using the contents of the present invention description and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A contact lens with variable structural color, characterized in that: The iris area and / or pupil area of ​​the contact lens has a wrinkle microstructure, the wrinkle microstructure is a periodically arranged micro-nanoscale convex structure and concave structure, the height of the convex structure or the concave structure is 1nm-100μm, and the period of the convex structure or the concave structure is 1nm-100μm; the wrinkle microstructure forms a structural color in the contact lens; The contact lens comprises a low modulus layer, a high modulus layer and a wrinkle microstructure, wherein the high modulus layer is distributed on one side or both sides of the low modulus layer, and the wrinkle microstructure is distributed on the outer surface of the high modulus layer; the modulus ratio of the high modulus layer to the low modulus layer is 2-1000; The method for preparing the contact lens with variable structural color comprises the following steps: (1) adding a contact lens precursor solution I into a contact lens mold, and polymerizing and curing the resulting contact lens to obtain a primary contact lens; (2) placing the contact lens precursor solution II and the contact lens primary sheet obtained in step (1) in a contact lens mold for secondary polymerization, and then polymerizing and curing the contact lens precursor solution II on the surface of the contact lens primary sheet to obtain a contact lens primary sheet having a periodic wrinkle microstructure; (3) Soaking the initial contact lens with a periodic wrinkled microstructure obtained in step (2) in saline to obtain a contact lens with a variable structural color.

2. The contact lens with variable structural color according to claim 1, characterized in that: The high modulus layer has a thickness of 1 nm-50 μm; the low modulus layer has a thickness of 10 nm-1000 μm.

3. The contact lens with variable structural color according to claim 1, characterized in that: In step (1), the contact lens precursor solution I is selected from (a) a solution containing a polymer; or (b) a polymerization solution containing a polymer monomer, an initiator and a cross-linking agent.

4. The contact lens with variable structural color according to claim 3, characterized in that: In step (1), the polymer is selected from polymethyl methacrylate, polyhydroxyethyl methacrylate, polymethacrylate-2-hydroxypropyl, polyethoxyethyl methacrylate, polyhydroxypropyl methylcellulose, polyhydroxymethyl cellulose, polydimethylaminoethyl methacrylate, polyethylene glycol dimethacrylate, polyisobornyl methacrylate, polycellulose acetate butyrate, polysiloxane methacrylate, polyfluorosilicone methacrylate, polyperfluoroether, poly N-vinyl pyrrolidone, polyvinyl alcohol, polyglycidyl methacrylate, silica gel, polydimethylsiloxane, polyparaxylene , polylactic acid, polyethylene glycol, polypropylene oxide, polycaprolactone-polyacrylic acid, polylactide, poly(lactide-glycolide), polyacrylamide, poly-N-isopropylacrylamide, collagen, gelatin, guar gum, polyphosphazene, sodium alginate, chitosan, hyaluronic acid, alginic acid, cellulose, agarose, polydextrose, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene sulfonic acid, polyvinyl phosphoric acid, choline, polyethylene oxide, polyethyleneimine, polyethyleneamine, polyvinylpyridine, polyphosphate, polysilicate, polyamino acid and fibrin, or any copolymer of any of the above.

5. The contact lens with variable structural color according to claim 3, characterized in that: In step (1), the initiator is selected from any one of an inorganic peroxide initiator, an azo initiator, a peroxide initiator and a photoinitiator.

6. The contact lens with variable structural color according to claim 3, characterized in that: In step (1), the cross-linking agent is selected from at least one of methylene bisacrylamide, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, divinyl benzene and derivatives thereof.

7. The contact lens with variable structural color according to claim 1, characterized in that: In step (2), the contact lens precursor solution II is selected from (a) a solution containing a polymer; or (b) a polymerization solution containing a polymer monomer, an initiator and a cross-linking agent.

8. The contact lens with variable structural color according to claim 7, characterized in that: In step (2), the polymer is selected from polymethyl methacrylate, polyhydroxyethyl methacrylate, polymethacrylate-2-hydroxypropyl, polyethoxyethyl methacrylate, polyhydroxypropyl methylcellulose, polyhydroxymethyl cellulose, polydimethylaminoethyl methacrylate, polyethylene glycol dimethacrylate, polyisobornyl methacrylate, polycellulose acetate butyrate, polysiloxane methacrylate, polyfluorosilicone methacrylate, polyperfluoroether, poly N-vinyl pyrrolidone, polyvinyl alcohol, polyglycidyl methacrylate, silica gel, polydimethylsiloxane, polyparaxylene , polylactic acid, polyethylene glycol, polypropylene oxide, polycaprolactone-polyacrylic acid, polylactide, poly(lactide-glycolide), polyacrylamide, poly-N-isopropylacrylamide, collagen, gelatin, guar gum, polyphosphazene, sodium alginate, chitosan, hyaluronic acid, alginic acid, cellulose, agarose, polydextrose, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene sulfonic acid, polyvinyl phosphoric acid, choline, polyethylene oxide, polyethyleneimine, polyethyleneamine, polyvinylpyridine, polyphosphate, polysilicate, polyamino acid and fibrin, or any copolymer of any of the above.

9. The contact lens with variable structural color according to claim 7, characterized in that: In step (2), the initiator is selected from any one of an inorganic peroxide initiator, an azo initiator, a peroxide initiator and a photoinitiator.

10. The contact lens with variable structural color according to claim 7, characterized in that: In step (2), the cross-linking agent is selected from at least one of methylene bisacrylamide, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, divinyl benzene and derivatives thereof.

11. The contact lens with variable structural color according to claim 1, characterized in that: In step (3), the brine is selected from any one of a sodium chloride aqueous solution with a mass fraction of 0.1%-10.0%, a sodium dihydrogen phosphate aqueous solution with a mass fraction of 0.1%-10.0%, and a disodium hydrogen phosphate aqueous solution with a mass fraction of 0.1%-10.0%.